Aggregation‐Induced Emission: Lighting up Cells, Revealing Life!. Issue 47 (4th September 2016) - Wang, Yi‐Feng; Zhang, Tingbin; Liang, Xing‐Jie
Abstract : Understanding metabolism and dynamic biological events in cells, as well as physiological functions and pathological changes in organisms, is the major goal of biological investigations. It will improve our capability to diagnose and treat diseases, and will enhance personalized medicine. Fluorescence imaging is a powerful tool that plays an essential role in acquiring the comprehensive knowledge necessary to help reach this goal. Fluorescent molecules are crucial factors for obtaining high quality images. In contrast to conventional fluorogens with aggregation‐caused quenching (ACQ) effect, molecules that show aggregation‐induced emission (AIE) effect open up new avenues for fluorescence imaging. So far, a large variety of AIE probes have been developed and applied to bioimaging because of their outstanding characteristics, such as high fluorescence efficiency, excellent photostability and high signal‐to‐noise ratio (SNR). In this review, recent advances in AIE‐based probes for biomedical imaging of intracellular microenvironments, natural macromolecules, subcellular organelles, intracellular processes, living tissues, and diagnosis and therapeutic evaluation of diseases in vivo are summarized. It is hoped that this review generates great research enthusiasm for AIE‐based bioimaging, in order to promote the development of promising AIE probes and guide us to a better understanding of the biological essence of life. Abstract : Aggregation‐induced emission (AIE) probes have recently been considered as alternatives in the area of biological imaging to reveal the mysteries of life. This review summarizes and describes typical AIE‐based probes for sensing intracellular microenvironments and natural macromolecules, lighting up subcellular organelles, tracking cellular processes, monitoring living tissues, improving the diagnosis of disease, and evaluating therapies.